Strengthening Community-Based Tourism through Eco-Edu Tourism Innovation in Baha Village - Suasih, Ni Nyoman Reni; Anandari, I Gusti Agung Ayu Apsari; Pratiwi, Ida Ayu Meisthya; Widiana, I Nyoman Wahyu; Sudharma, I Wayan Priyana Agus; Yasa, I Made Putra; Putra, I Putu Reza Krisna; Andriani, Ni Luh Ayu Dessy (Research Collaboration Community (Rescollacom), 2025)
This community engagement programme aimed to enhance the capacity of tourism practitioners in Baha Tourism Village, located in Badung Regency, by adopting an eco-edu tourism innovation approach. Although Baha Village possesses strategic potential as a tourist destination, it currently faces three primary challenges: suboptimal institutional structures and human resources, limited innovation in tourism products, and weak marketing strategies. The activities conducted included educational outreach, focus group discussions (FGDs), and assessments of participants’ understanding through pre-tests and post-tests. The content focused on institutional strengthening, the development of tourism products based on local potential, and strategies for digital branding and marketing. The results indicated a significant improvement in participants' understanding of eco-edu tourism concepts and management practices. In addition, several innovative ideas for tourism development emerged, such as the creation of an educational flower garden and the exploration of wellness tourism opportunities. Evaluation of the programme also showed a positive response from participants, in terms of content quality, enthusiasm for further learning, and a strong commitment to applying the acquired knowledge. This initiative is expected to serve as an initial step towards the revitalisation of Baha Tourism Village, while also offering a potential model for sustainable village tourism development that directly empowers local communities.